ON CERTAIN ISSUES OF TESTAMENTARY INHERITANCE IN SERBIAN LAW – DE LEGE FERENDA (PART I) - Vidić , Jelena; Kovačević, Milica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The validity of a will is conditioned by the existence of the testamentary capacity at the time of its creation, existence of certain qualities regarding the testator’s will, as well as the the requirement that the will of the testator must be expressed in the form and under the conditions provided by law. The аticle primarily focuses on certain substantive legal assumptions of the validity of will, as well as on formal legal assumptions of its validity, specifically, on the testamentary capacity and forms of will, and the prescribed form requirements regarding existing forms of will, i.e. the conditions under which they can be made. By analyzing the current statutory provisions that are dedicated to the mentioned issues, from the point of view of the ruling doctrinal positions, as well as legal solutions accepted in other countries, certain deficiencies are identified in their legislation as well as in the application of these solutions in legal practice. In the paper, the authors propose the necessary changes and supplements in order to obtain a higher quality, as well as a more comprehensive way of regulating the analyzed institutes in the domain of the testamentary inheritance.